Self-Islah, Gender Relation and Socio-Economic Challenges on Tablighi Jamaat Proselytization Practices in Indonesia - Saipul Hamdi; Fadli Mulyadi; Fanny Henry Tondo; Ahmad Muzayyin (Graduate Program of Pontianak Institute of Islamic Studies, 2021)
This article explores one of the Tablighi Jamaat (TJ) teachings self-islah that develops in its dawah practices. Self-Islah emphasizes improving oneself through a proselytization program called khuruj from one community to another, from one mosque to another. The phenomenon of TJ dawah shows a different approach and pattern where da’i play dual roles not only as subject (preachers) but also as an object (listeners) during that khuruj program. Self-islah in this context includes strengthening faith, morals, and gender awareness. The gender aspect is strong external critics of TJ religious tradition where it does not involve women in their religious activities and even avoids interacting with them. Thus, TJ members must handle all the needs while staying in the mosque for religious camps, such as washing clothes, cooking, washing dishes, and serving guests from the local and international community. The article investigates changes in gender relations within the TJ family in the post-khuruj program. This article also focuses on the economic challenges Tablighi members face when they go out of preaching (khuruj), especially those from the lower-middle class. The research findings show that most TJ members achieved self-Islah and hugely impacted the evolution of spirituality after khuruj. They also acknowledged the transformation of gender relations in the family, but on another side, facing economic crises due to prioritizing dawah activity. I used an ethnographic approach and applied a qualitative method in collecting and analyzing data for two years (2017-2018) in three research locations, Lombok, Balikpapan, and Jakarta.